High Spin Structure of 122Xe - Serris, M.; et al., - (HNPS Advances in Nuclear Physics, 2020)
High spin states in the isotope 122Xe were populated using the reaction 96Zn(30Si,2n)122Xe at a beam energy of 135 MeV. The subsequent γ-ray deexcitation was studied using γ-ray spectroscopic methods. The analysis of γ-γ coincidences has revealed two new structures of competing dipole and quadrupole transitions. The highest states of a positive parity band provide characteristics consistent with an approach to band termination.